ChemInform Abstract: Pd‐N‐Heterocyclic Carbene Catalyzed Synthesis of Piperidine Alkene—Alkaloids and Their Anticancer Evaluation. Issue 31 (5th August 2014) - Kankala, Shravankumar; Kankala, Ranjith Kumar; Balaboina, Ramesh; Thirukovela, Narasimha Swamy; Vadde, Ravinder; Vasam, Chandra Sekhar
Abstract Optimum reaction conditions are examined for the Heck reaction of (I) with various aromatic alkenes which is the key step to synthesize the 10 title compounds of type (IV).